2018
DOI: 10.1016/j.foodchem.2017.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple, low cost chronoamperometric assay for fructose based on a commercial graphite-nanoparticle modified screen-printed carbon electrode

Abstract: 10This paper describes the development of a simple, low cost chronoamperometric assay, for the measurement of 11 fructose, using a graphite-nanoparticle modified screen-printed electrode (SPCE-G-COOH). Cyclic voltammetry 12showed that the response of the SPCE-G-COOH enhanced the sensitivity and precision, towards the enzymatically 13 generated ferrocyanide species, over a plain SPCE; therefore the former was employed in subsequent studies.14 Calibration studies were carried out using chronoamperometry with a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…After the appearance of novel conducting polymers, ionic liquids and other carbon-based materials, the scientific community has tried to implement them for the development of a reliable screen-printed reference electrode not necessarily of the Ag/AgCl type. Although in the past, Ag/AgCl reference electrode seemed to be the most promising type of screen-printed reference electrodes, nowadays most scientists have moved to other directions such as ionophore-doped membranes using ionic liquids, nanomaterials [57], solid ion-conducting materials such as Nafion™ and more commonly, conducting polymers. Conducting polymers feature several advantages since they are in the solid form, can conduct electricity with very low currents and have low impedances, they are low-cost and they can be used as screen-printing inks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the appearance of novel conducting polymers, ionic liquids and other carbon-based materials, the scientific community has tried to implement them for the development of a reliable screen-printed reference electrode not necessarily of the Ag/AgCl type. Although in the past, Ag/AgCl reference electrode seemed to be the most promising type of screen-printed reference electrodes, nowadays most scientists have moved to other directions such as ionophore-doped membranes using ionic liquids, nanomaterials [57], solid ion-conducting materials such as Nafion™ and more commonly, conducting polymers. Conducting polymers feature several advantages since they are in the solid form, can conduct electricity with very low currents and have low impedances, they are low-cost and they can be used as screen-printing inks.…”
Section: Discussionmentioning
confidence: 99%
“…Salt matrix A wide variety of voltammetric, amperometric and potentiometric sensors have been reported that implement QREs while they have also been used in cyclic voltammetry. The construction and fabrication of Ag/AgCl QREs has been achieved by different approaches and on several different types of substrates, each one serving the specific application [49], [57]- [61]. Choi et al in 2001 [62], developed a screen-printed disposable sensor for the anodic stripping voltammetric (ASV) analysis of heavy metals.…”
Section: Reference Electrodementioning
confidence: 99%
“…We were taken screen printed electrode and modifying them using different materials. In past few years many nano-materials was used for modifying electrodes [32], [47], [70]. After modifying samples are performed on that electrode using following equation: X 1 + HClO 4 X 2 + Cl -Here we mixed X1 solvent into HClO 4 solution at different terms and conditions and performed electrochemical experiment.…”
Section: Discussion Of Studymentioning
confidence: 99%
“…Furthermore, these electrodes are appropriate for operations with micro volumes and decentralized assays (point of care tests), and so forth. [19][20][21][22][23] To minimize the oxidation over-potential of numerous electroactive compounds, researchers designed the electrocatalytic procedures for exploitation at the modied electrode surface. Notably, the chemically modied electrodes augment the transfer rate of electrons by declining the over-potential.…”
Section: Introductionmentioning
confidence: 99%